Effects of Dietary Inosine 5'-Monophosphate Supplementation on the Growth Performance and Salinity and Oxidative Stress Resistance of Gibel Carp (Carassius auratus gibelio) - Luohai Hua; Peiyu Zhang; Haokun Liu; Mingze Xin; Zhiwei Zhang; Dong Han; Zhimin Zhang; Xiaoming Zhu; Junyan Jin; Yunxia Yang; Shouqi Xie (MDPI AG, 2024)
An 88-day feeding trial was conducted to evaluate the effects of dietary inosine 5'-monophosphate (5'-IMP) on the growth performance and salinity and oxidative stress resistance in the juvenile gibel carp CAS III (Carassius auratus gibelio; initial body weight: 7.48 g). Four isonitrogenous and isoenergetic diets containing exogenous 5'-IMP were formulated. P1, P2, P3 and P4 were diets containing 5'-IMP at four concentrations (0, 1, 2 and 4 g kg−1). The four diets were randomly allotted to triplicate tanks in a recirculating system. After the feeding trial, six fish per tank were netted randomly and placed into 12‰ saline water to test their response to salinity stress. The results indicated that the feed conversion rate was enhanced by dietary supplementation with 5'-IMP. The appetite, plasma neuropeptide Y level and feeding rate of the P3 group were lower than those in the control treatment group. Dietary supplementation with 5'-IMP improved the osmoregulatory adaptation of gibel carp under acute salinity stress. Six hours after the salinity stress treatment, in the dietary 5'-IMP treatment group, the plasma cortisol and K+ concentrations were lower and the Na+/K+-ATPase activity was greater than that in the control group. Dietary supplementation with 5'-IMP promoted the expression of the glucocorticoid receptors NKA-α1b and NKCC and retarded the expression of Hsp70 in P4-treated gill filaments and kidneys. Dietary supplementation with 5'-IMP resulted in a stable oxidative-stress-resistant phenotype characterized by increased levels of cellular antioxidants, including SOD, catalase, glutathione peroxidase, glutathione reductase and MPO. The above results of the current study demonstrate that supplementation of 5'-IMP can promote feed utilization and have positive influences on the salinity and oxidative stress resistance of gibel carp.